Heterogeneous Genetic Diversity Estimation of a Promising Domestication Medicinal Motherwort Leonurus Cardiaca Based on Chloroplast Genome Resources - Sun, Jiahui; Wang, Yiheng; Garran, Thomas Avery; Qiao, Ping; Wang, Mengli; Yuan, Qingjun; Guo, Lanping; Huang, Luqi (Frontiers in Genetics, 2021)
Leonurus cardiaca has a long history of use in western herbal medicine and is applied for the treatment of gynaecological conditions, anxiety, and heart diseases. Because of its botanical relationship to the primary Chinese species, L. japonicus, and extensive medical indications that go beyond the traditional indications for the Chinese species, it is a promising medicinal resource. Therefore, the features of genetic diversity and variability in the species have been prioritized. To explore these issues, we sequenced the chloroplast genomes of 22 accessions of L. cardiaca from different geographical locations worldwide using high-throughput sequencing. The results indicate that L. cardiaca has a typical quadripartite structure and range from 151236 bp to 151831 bp in size, forming eight haplotypes. The genomes all contain 114 distinct genes, including 80 protein-coding genes, 30 transfer RNA genes and four ribosomal RNA genes. Comparative analysis showed abundant diversity of single nucleotide polymorphisms (SNPs), indels, simple sequence repeats (SSRs) in 22 accessions. Codon usage showed highly similar results for L. cardiaca species. The phylogenetic and network analysis indicated 22 accessions forming four clades that were partly related to the geographical distribution. In summary, our study highlights the advantage of chloroplast genome with large data sets in intraspecific diversity evaluation and provides a new tool to facilitate medicinal plant conservation and domestication.